Macular assessment using Optical Coherence Tomography in patients after uneventful phacoemulsification treated postoperatively with bromfenac, diclofenac or dexamethasone - Gołębiewska, Joanna; Ciszewska, Joanna; Kopacz, Dorota; Turczyńska, Monika; Kęcik, Dariusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Aim : To assess macular thickness and volume using optical coherence tomography in patients treated with different anti-inflammatory agents after uneventful phacoemulsification. Material and methods : We analysed macular parameters using optical coherence tomography in 50 consecutive patients (mean age 70.5 years) who underwent uneventful phacoemulsification cataract surgery at the Ophthalmology Department, Medical University of Warsaw between March 2012 and January 2013. Patients were divided into 3 groups, according to 3 different anti- -inflammatory agents used during the postoperative period: group T receiving dexamethasone 0.1% (n=17), group Y receiving bromfenac sodium 0.09% (n=16) and group D receiving diclofenac sodium (n=17). We evaluated macular scans obtained the day before surgery and on days 1., 7., 30. and 90. postoperatively. Central subfield thickness, cube volume and cube average thickness were measured during the optical coherent tomography. The data was analysed statistically using the SAS 9.2 software. The graphs were prepared using the STATISTICA 12 software. Results : A significant increase in central subfield thickness was observed on day 30. postoperatively. However, there were no statistically significant differences in macular thickness between the study groups. Conclusions : Central retinal thickness increases after uneventful phacoemulsification despite active anti-inflammatory treatment and irrespective of the drug class used.